Maternal complications of menstrual regulation - Biswas, SP; Begum, B; Bakshi, KK (Bangladesh Medical Journal Khulna, 2012)
This prospective observational study was done in Obstetrics and Gynecology unit in Kalaroa Health Complex, Kalaroa & Sadar Hospital, Satkhira from 1st January 2009 to 30th June 2010. The aim of it was to evaluate complications due to menstrual regulation (MR) risk factors for complications, immediate morbidities and mortality & management pattern. Total number of admission was 773, out of which only MR complications was 6.46%. Within this group, 96% patients belonged to 20 to 40 years age group, 84% were multipara. Gestational age in between 7 to 9 weeks was recorded in 72% and in 50% cases, MR was performed in private chamber, 12% patients was suffering from only pervaginal bleeding with nonfatal complications. Shock and acute abdomen due to visceral injury was 26% in which abdominal surgery was done in 12% cases. 94% patients improved after comprehensive management. Death was recorded in 6% cases. MR complications still remain an important cause of maternal morbidities and mortality in Bangladesh. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10469 Bang Med J (Khulna) 2011: 44(1&2) 11-14